2010
DOI: 10.1186/1471-2334-10-200
|View full text |Cite|
|
Sign up to set email alerts
|

EVOTECH® endoscope cleaner and reprocessor (ECR) simulated-use and clinical-use evaluation of cleaning efficacy

Abstract: BackgroundThe objective of this study was to perform simulated-use testing as well as a clinical study to assess the efficacy of the EVOTECH® Endoscope Cleaner and Reprocessor (ECR) cleaning for flexible colonoscopes, duodenoscopes, gastroscopes and bronchoscopes. The main aim was to determine if the cleaning achieved using the ECR was at least equivalent to that achieved using optimal manual cleaning.MethodsSimulated-use testing consisted of inoculating all scope channels and two surface sites with Artificial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 24 publications
1
20
0
2
Order By: Relevance
“…Alfa et al reported that automated cleaning resulted in 98.8% of surfaces and 99.7% of lumens meeting or surpassing cleaning end-points for protein, hemoglobin, and bioburden residuals. 38 Similar results have been reported with other automated cleaning machines. 39 The mandating of automated cleaning remains under review.…”
Section: Cpe Infection Control Endoscopysupporting
confidence: 83%
“…Alfa et al reported that automated cleaning resulted in 98.8% of surfaces and 99.7% of lumens meeting or surpassing cleaning end-points for protein, hemoglobin, and bioburden residuals. 38 Similar results have been reported with other automated cleaning machines. 39 The mandating of automated cleaning remains under review.…”
Section: Cpe Infection Control Endoscopysupporting
confidence: 83%
“…Evaluation of the EVOTCH system documented the attainment or surpassing of cleaning endpoints for protein, hemoglobin, and bioburden residuals for 98.8% of the surfaces and 99.7% of lumens in the clinical study. It also demonstrated the attainment or surpassing of cleaning endpoints for protein and bioburden residuals for 100% of endoscopes and bronchoscopes in the simulated-use study 34. Assessment of the cost-efficiency of the ECR approaches in an actual practice setting demonstrated a significantly shorter time of endoscope reprocessing and reduced cost compared with manual cleaning followed by automated reprocessing.…”
Section: Aermentioning
confidence: 94%
“…Recent independent company-sponsored studies also demonstrate significant clearance of protein and other bioburden. 49 Another reprocessor and disinfectant combination was recently cleared with labeling for high-level disinfection after attenuated washing and brushing (OERPro; Olympus America, Center Valley, Pa). These technologies and those still to come warrant further well-designed, peer-reviewed studies by using commercially available machines in clinical settings.…”
Section: Unresolved Issues Requiring Further Studymentioning
confidence: 99%